2018 IEEE International Conference on Healthcare Informatics Workshop (ICHI-W) 2018
DOI: 10.1109/ichi-w.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Signals of Associations Between Dietary Supplement Use and Mental Disorders from Twitter

Abstract: In this study, we attempted to detect signals of association between dietary supplement use and mental disorders from Twitter. We collected tweets ranging from 2016 to 2017 which mention five dietary supplements. A case cohort of 257 users were identified by adapting a natural language processing method with further manually verified to have taken one supplement. We then randomly selected 257 users who had not taken any dietary supplement as the control cohort and compared the sentiment and mental health signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…Wang et al have focused on depression, a primary reason for suicide that can be analyzed through the natural language analysis of the written text [4]. In this work, the authors have used Reddit posts to determine the parameters that indicate depressions.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al have focused on depression, a primary reason for suicide that can be analyzed through the natural language analysis of the written text [4]. In this work, the authors have used Reddit posts to determine the parameters that indicate depressions.…”
Section: Related Workmentioning
confidence: 99%
“…15 Several studies have developed methods for the creation of DS terminology and knowledge base as well as the detection of DS-associated AEs from different data sources. [16][17][18][19][20][21][22] For example, we have extracted and standardized DS information from online sources to build an integrated DS knowledge base, (ie, iDISK). 23 And we demonstrated that as compared with the UMLS, DS terminology in the iDISK contains more novel synonyms, and achieved a better performance in a DS NER task on biomedical literature.…”
Section: Introductionmentioning
confidence: 99%
“…18 We developed methods to extract the DS usage information from Twitter, and assessed the association between DS use and mental disorders (eg, anxiety, depression). 19 We also mined AEs from DS product labels in the Dietary Supplement Label Database using topic modeling. 20 In addition, we developed a rule-based NLP system to normalize DS product names in the Dietary Supplement Label Database.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations